2013
DOI: 10.1093/brain/awt099
|View full text |Cite
|
Sign up to set email alerts
|

A functional magnetic resonance imaging study mapping the episodic memory encoding network in temporal lobe epilepsy

Abstract: Functional magnetic resonance imaging has demonstrated reorganization of memory encoding networks within the temporal lobe in temporal lobe epilepsy, but little is known of the extra-temporal networks in these patients. We investigated the temporal and extra-temporal reorganization of memory encoding networks in refractory temporal lobe epilepsy and the neural correlates of successful subsequent memory formation. We studied 44 patients with unilateral temporal lobe epilepsy and hippocampal sclerosis (24 left) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
154
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 134 publications
(176 citation statements)
references
References 60 publications
18
154
3
1
Order By: Relevance
“…Some studies found preoperative reorganization of verbal memory to the ipsilateral posterior hippocampus and extratemporally (orbitofrontal and anterior cingulate cortex in the left and superior temporal gyri bilaterally in the right MTLE). Postoperatively, however, the reorganization of memory to the contralateral hippocampus seems to be the main compensatory mechanism [48]. In MTLE patients, there are data indicating that frontal lobe-related cognitive functions improve after temporal lobe resections.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found preoperative reorganization of verbal memory to the ipsilateral posterior hippocampus and extratemporally (orbitofrontal and anterior cingulate cortex in the left and superior temporal gyri bilaterally in the right MTLE). Postoperatively, however, the reorganization of memory to the contralateral hippocampus seems to be the main compensatory mechanism [48]. In MTLE patients, there are data indicating that frontal lobe-related cognitive functions improve after temporal lobe resections.…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges to the elucidation of AD etiology is the difficulty in studying the earliest changes in the evolution of disease and correlating these with antemortem cognitive and behavioral functions. Cognition and memory are the products of the integrated activity in cortical networks of various hubs/regions (Friston et al 1993;Horwitz 1994;McIntosh 1999;Grady et al 2001;Yonelinas et al 2005); these attributes may decline following disruption in network interactions due to sensory disruptions (Grady et al 2001;Sidhu et al 2013). An ongoing temporal course of sensory dysfunction may lead to dysfunction in the projected nuclei, as well as corticocortical neurocircuitry; this may thus underpin white and gray matter atrophy in the pathogenesis of AD (Greicius et al 2004;Jones et al 2016;Teipel et al 2016).…”
Section: Neurotox Resmentioning
confidence: 99%
“…Understanding Memory Systems in TLE: Networks, Nodes, and Hubs reorganization/compensatory effects of the brain when faced with pathological processes (5).…”
Section: Commentarymentioning
confidence: 99%